Monoolein-based nanoparticles containing indinavir: a taste-masked drug delivery system. (2nd January 2021) - Bianchin, Mariana Domingues; Prebianca, Germano; Immich, Maira Frielink; Teixeira, Mário Lettieri; Colombo, Mariana; Koester, Leticia Scherer; Araújo, Bibiana Verlindo de; Poletto, Fernanda; Külkamp-Guerreiro, Irene Clemes
Abstract: Objective: This study developed a novel child-friendly drug delivery system for pediatric HIV treatment: a liquid, taste-masked, and solvent-free monoolein-based nanoparticles formulation containing indinavir (0.1%). Significance: Adherence to antiretroviral therapy by pediatric patients is difficult because of the lack of dosage forms adequate for children. Methods: Monoolein-based nanoparticles were developed. The particle size, zeta potential, pH, drug content, small angle X-ray scattering, stability, in vitro drug release profile, biocompatibility, toxicity, and taste-masking properties were evaluated. Results: Monoolein-based formulations containing indinavir had nanosized particles with 155 ± 7 nm, unimodal particle size distribution, and polydispersity index of 0.16 ± 0.03. The zeta potential was negative (−31.3 ± 0.3 mV) and pH was neutral (7.78 ± 0.01). A 96% drug incorporation efficiency was achieved, and the indinavir concentration remained constant for 30 days. Polarized light microscopy revealed isotropic characteristics. Transmission electron microscopy images showed spherical shaped morphology. Small-angle X-ray scattering displayed a form factor broad peak. Indinavir had a sustained release from the nanoparticles. The system was nonirritant and was able to mask drug bitter taste. Conclusions: Monoolein-based nanoparticles represent a suitable therapeutic strategy for antiretroviral treatment with the potential to reduce the frequency of drug administration and promote pediatric adherence.